Secularism and Religious Education in India - Pateria, Varlaxmi; Pateria, A K (Journal of Dharma, 1984)
The issue of religious education has been raised on several occasions in pre-and post-independence India but has always been abandoned in the end, without arriving at any definite conclusions. This is partly due to the excessive stress laid on rational, scientific and technological education and partly to an erroneous and vague understanding of secularism, which India has promulgated as its key principle along with the acceptance of democracy. The present paper attempts to examine the concept of secularism as stated in the Constitution of India and to examine the permissibility of religious education within its scope.